ANALYSIS OF LEJO PUTERI MAS WOVEN FABRIC BUSINESS ON THE ECONOMY OF THE PEOPLE OF BENGKALIS REGENCY, RIAU - Hasan, Zulfikar (Universitas Cenderawasih, 2024)
This study aims to determine the impact of the Lejo Mas woven cloth business on the community's economy in Sebauk Village, Bengkalis District, Bengkalis Regency. data was carried out using interviews and documentation methods, and data analysis techniques were carried out using primary data and secondary data, the results of the research showed the impact felt by the community on the development of the Lejo Puteri Mas Woven Cloth business, is hoped that the per capita income of the community will also increase so that the Lejo Puteri Mas Woven Cloth business can have a significant impact on the economy of the Sebauk village community. The economic growth of the people in Sebauk Village is getting better developing the economy by utilizing the local potential they have. It is hoped that the per capita income of the community will also increase so that the Lejo Puteri Mas woven cloth business can have a significant impact on the economy of the people of Sebauk Village.